PENGARUH PELAKSANAAN PENILAIAN PRESTASI TERHADAP KINERJA KARYAWAN - Asdarini "; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was conducted at PT. Asuransi Wahana Tata Cabang Pekanbaru is located on Jl. Jend Sudirman No.374, Pekanbaru Riau, which is a company enganged in insurance. The purpose of this study wor to determine the effect of the implementation of the performance evaluation of employed performance on Asuransi Wahana Tata cabang Pekanbaru. The research methods include the location of the research conducted at Asuransi Wahana Tata Cabang Pekanbaru, types and sources of data used was primer data, where the data was obtained directly from the company, among others target achievment of data and premi realization and the number of polis from the years 2011-2013, and a general over view of the company, while the analysis of the data using descriptive statistical analysis method that uses a simple liniear regelasi analysis, correlation test, test coefficient of determination.Based on the research that has been dot cant be obtained correlation r=0,721 it this stated variable free and of determinationcoeficient R Squaare of 0,520. That is the fulfillment of a variable contribution of achievment by 52% while the remaining 48% in influenced by other variable not induded in this study. And dont test reults are t (4, 417>t table (2,101)and sig (0,000)< 0,05. This means performance appraisal were significant affect on the performance of employees.From the research, leader should be cultivated asuransi wahana tata cabang pekanbaru cant pay more attention to it this employees at work, with the hope that future employees can have high work, that will postively impact the company.Keyword:achivmentassessment,empl oyed, PT. Asuransi Wahana Tata